A narrative review of psychiatric features of traumatic encephalopathy syndrome as conceptualized in the 20th century - Iverson, Grant L.; Kissinger-Knox, Alicia; Huebschmann, Nathan A.; Castellani, Rudolph J.; Gardner, Andrew J. (Frontiers in Neurology, 2023)
Introduction Some ultra-high exposure boxers from the 20th century suffered from neurological problems characterized by slurred speech, personality changes (e.g., childishness or aggressiveness), and frank gait and coordination problems, with some noted to have progressive Parkinsonian-like signs. Varying degrees of cognitive impairment were also described, with some experiencing moderate to severe dementia. The onset of the neurological problems often began while they were young men and still actively fighting. More recently, traumatic encephalopathy syndrome (TES) has been proposed to be present in athletes who have a history of contact (e.g., soccer) and collision sport participation (e.g., American-style football). The characterization of TES has incorporated a much broader description than the neurological problems described in boxers from the 20th century. Some have considered TES to include depression, suicidality, anxiety, and substance abuse. Purpose We carefully re-examined the published clinical literature of boxing cases from the 20th century to determine whether there is evidence to support conceptualizing psychiatric problems as being diagnostic clinical features of TES. Methods We reviewed clinical descriptions from 155 current and former boxers described in 21 articles published between 1928 and 1999. Results More than one third of cases (34.8%) had a psychiatric, neuropsychiatric, or neurobehavioral problem described in their case histories. However, only 6.5% of the cases were described as primarily psychiatric or neuropsychiatric in nature. The percentages documented as having specific psychiatric problems were as follows: depression = 11.0%, suicidality = 0.6%, anxiety = 3.9%, anger control problems = 20.0%, paranoia/suspiciousness = 11.6%, and personality change = 25.2%. Discussion We conclude that depression, suicidality (i.e., suicidal ideation, intent, or planning), and anxiety were not considered to be clinical features of TES during the 20th century. The present review supports the decision of the consensus group to remove mood and anxiety disorders, and suicidality, from the new 2021 consensus core diagnostic criteria for TES. More research is needed to determine if anger dyscontrol is a core feature of TES with a clear clinicopathological association. The present findings, combined with a recently published large clinicopathological association study, suggest that mood and anxiety disorders are not characteristic of TES and they are not associated with chronic traumatic encephalopathy neuropathologic change.